Determinants of Trade Union Membership in Western Germany: Evidence from Micro Data, 1980-2000 - Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2003)
An empirical analysis of various waves of the ALLBUS social survey shows that union density fell substantially in West Germany from 1980 to 2000. Such a negative trend can be observed for men and women and for different groups of the workforce. Repeated crosssectional analyses suggest that a number of personal, occupational and attitudinal variables such as sex, occupational status, firm size and political orientation play a role in the unionization process, although the influence of many variables is not robust over time. While the results are consistent with cost-benefit considerations on the sides of employees and unions, individualization theory and social custom theory is not consistently supported by our estimations.
Keywords: J51; 330; trade union membership; Germany; micro data; Gewerkschaft; Mitgliedschaft; Kosten-Nutzen-Analyse; Alte Bundesländer; Deutschland